Methods and Principles of Music Therapy Intervention in Sleep Disorders - Gao, Xinnuan (International Journal of Public Health and Medical Research, 2025)
Nowadays, the problem of sleep disorders is becoming more and more obvious around the world, which has attracted widespread attention. At present, the main solution to this problem is drug therapy, however, there are still many adverse effects of drug treatment, and some people have proposed that non-drug therapies such as music therapy can improve sleep quality. In this work, it will summarize how music therapy treats sleep disorders, reveal its internal mechanism, and this article also compares the differences between Chinese and Western music therapy interventions for sleep disorders. Finally, it looks forward to future research to look for shortcomings.